The Role of Largest Ownership Structure in ESG Reporting, Tax Avoidance, and Firm Value: Evidence from Emerging Markets - Dianwicaksih Arieftiara; Shinta Widyastuti; Masripah Masripah; Munasiron Miftah; Suparna Wijaya (Qubahan Academic Journal)
The level of concern among business entities regarding sustainability issues in emerging markets remains minimal, particularly in Indonesia and Malaysia. The intention to fulfill the requirement is contingent upon the owner's intention, as ESG reporting is a non-financial information that is naturally considered a business ethic. Consequently, this study investigates the influence of ownership structure on Environmental, Social, and Governance (ESG) reporting, tax avoidance, and firm value. This study expands to investigate the impact of ESG reporting on tax avoidance and firm value in Indonesia and Malaysia, as sustainability initiatives could potentially be used as a strategy for tax avoidance. We find the largest ownership structure and check to see if all of its members add to the value of the company. This lets us figure out how much these large shareholders affect the company's tax and sustainability plans. We focus on all non-financial sector companies that have published ESG Reporting in Indonesia and Malaysia from 2012 to 2023. We apply moderated panel regressions to test our hypotheses. Our findings reveal that the largest ownership in Indonesia negatively influences ESG reporting but positively affects tax avoidance, while the largest ownership in Malaysia has no significant effect on ESG disclosure or tax avoidance. The supervision of the largest owner of ESG reporting significantly affects tax avoidance in both countries. The supervision of the largest ownership structure in ESG reporting also has a significant impact on firm value. Meanwhile, the supervision of the largest owner of tax avoidance does not impact firm value. This is the first study to investigate at how the largest ownership structure of companies in both countries oversee the creation of sustainability programs that meet the requirements for sustainability reporting while also being used as tax strategies and increase the value of the company.